Integrated QTL mapping and candidate gene analysis for yield-related traits and salt tolerance in a rice RIL population - Zhang, Yanhong; Wang, Yulong; Du, Xiaojing; Wen, Xiaorong; Kang, Mintai; Hou, Tianyu; Tang, Fusen; Qi, Yuhong; Zhao, Zhiqiang; Yuan, Quan; Bhaliqem, Abliz; Li, Dong; et al. (Frontiers in Plant Science, 2026)
Rice is a globally critical staple crop, and enhancing its yield and stress resilience is essential for food security. In this study, we employed a recombinant inbred line (RIL) population derived from cultivars Liangxiang5 and 03GY28 to dissect the genetic basis of yield-related traits, leaf color, and germination stage salt tolerance. A high-density genetic map was constructed using 1, 101 bin markers, spanning 1, 132.95 cM with an average marker interval of 1.03 cM. Over two-year field trials, we identified 16 quantitative trait loci (QTLs) for nine agronomic traits distributed across chromosomes 3, 5, 6, 7, 9, and 11. These QTLs accounted for 5.48%-19.03% of phenotypic variance (PVE), with LOD scores ranging from 2.52 to 8.93. Notably, a major-effect QTL, qLeafColor9.1, explaining 19.03% of variance and was mapped to chromosome 9 and co-localized with the known senescence-associated gene OsSGR, which was significantly upregulated under salt stress. Additionally, QTL hotspots on chromosomes 9 and 11 governed multiple yield-related traits-including panicle branching number, filled grain number, and total grain number-including pleiotropy or tight gene linkages. Additionally, two salt tolerance-related QTLs (qRSDR6.1 and qRSDR7.1) were identified, and candidate genes responsive to abiotic stress were annotated within these intervals. These findings advance our understanding of the genetic architecture underlying rice agronomic traits and provide actionable targets for marker-assisted breeding to improve yield, stress tolerance, and grain quality.